If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -15 = -123 Reorder the terms: -15 + -6x = -123 Solving -15 + -6x = -123 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -6x = -123 + 15 Combine like terms: -15 + 15 = 0 0 + -6x = -123 + 15 -6x = -123 + 15 Combine like terms: -123 + 15 = -108 -6x = -108 Divide each side by '-6'. x = 18 Simplifying x = 18
| 5X-3+6X-8-9X-1=-3X | | -24=6+5x | | 2.6q-3.9-5.7q=-4.1q-1.3 | | 3/2x=30 | | 36x61/45 | | 15x+2+x=18x+90-2x | | y-28=-41 | | -5y+5=-6y+2 | | 3/5s=12 | | 8(t-5)+7t=5(3t+5)-13 | | 1/2x1/9 | | 2+15x-21=14x-22 | | 1/2*1/9 | | -33p=-264 | | 2+15x-21=13x-22 | | Y-45=11 | | -2(2x-3)-(2x-6)+5=-5(x-1)-(2x+6)+3 | | y=-4x-31 | | a=5-9a+8 | | 6x+8y-2x-y= | | 3/4=87*9 | | 7x-12-2x=7x-9 | | (x-1)+(2x+3)+(2x+3)=180 | | 9=87/3/4 | | 15x-.75=13x-.50 | | 87=3/4/9 | | 15x/2+19=12x+7/2 | | 14/19/11 | | 9x^4-10x^2+1=0 | | 1(t-3)+7t=4(2t+4)-13 | | x=0.40(x+15) | | 76c=828 |